Cosmopolitan Ideal in Timothy Mo’s An Insular Possession - Shenghao Hu; Zengxin Ni (Humanities)
Hong Kong-born British writer Timothy Mo’s novel An Insular Possession (1986) focuses on the First Opium War (1839–1842) and critically examines global inequalities. This article explores cosmopolitanism as a potential framework for mitigating cross-cultural conflicts. Instead of embracing cosmopolitanism as an inherently positive vision, the novel critiques two cosmopolitan worldviews—British colonialism and the Chinese Tianxia concept—and reveals the potential complicity of cosmopolitanism in consolidating hierarchical world orders. Through the protagonist Gideon Chase, an American expatriate engaged in studying Chinese language and culture, Mo envisions a de-colonial cosmopolitan vision that seeks to transcend the center/margin dynamic and fosters more equitable cross-cultural interactions. Gideon’s ultimate failure to alleviate Sino–British tensions prompts reflections on global justice and underscores the urgent need to establish a cosmopolitan world order marked by peace, mutual respect and tolerance of difference.